Calorimetric and spectroscopic studies of the thermotropic phase behavior of lipid bilayer model membranes composed of a homologous series of linear saturated phosphatidylserines. - Lewis, R N (2000)
The thermotropic phase behavior of lipid bilayer model membranes composed of the even-numbered, N-saturated 1,2-diacyl phosphatidylserines was studied by differential scanning calorimetry and by Fourier-transform infrared and (31)P-nuclear magnetic resonance spectroscopy. At pH 7.0, 0.1 M NaCl and in the absence of divalent cations, aqueous dispersions of these lipids, which have not been incubated at low temperature, exhibit a single calorimetrically detectable phase transition that is fully reversible, highly cooperative, and relatively energetic, and the transition temperatures and enthalpies increase progressively with increases in hydrocarbon chain length. Our spectroscopic observations confirm that this thermal event is a lamellar gel (L(beta))-to-lamellar liquid crystalline (L(alpha)) phase transition. However, after low temperature incubation, the L(beta)/L(alpha) phase transition of dilauroyl phosphatidylserine is replaced by a higher temperature, more enthalpic, and less cooperative phase transition, and an additional lower temperature, less enthalpic, and less cooperative phase transition appears in the longer chain phosphatidylserines. Our spectroscopic results indicate that this change in thermotropic phase behavior when incubated at low temperatures results from the conversion of the L(beta) phase to a highly ordered lamellar crystalline (L(c)) phase. Upon heating, the L(c) phase of dilauroyl phosphatidylserine converts directly to the L(alpha) phase at a temperature slightly higher than that of its original L(beta)/L(alpha) phase transition. Calorimetrically, this process is manifested by a less cooperative but considerably more energetic, higher-temperature phase transition, which replaces the weaker L(beta)/L(alpha) phase transition alluded to above. However, with the longer chain compounds, the L(c) phase first converts to the L(beta) phase at temperatures some 10-25 degrees C below that at which the L(beta) phase converts to the L(alpha) phase. Our results also suggest that shorter chain homologues form L(c) phases that are structurally related to, but more ordered than, those formed by the longer chain homologues, but that these L(c) phases are less ordered than those formed by other phospholipids. These studies also suggest that polar/apolar interfaces of the phosphatidylserine bilayers are more hydrated than those of other glycerolipid bilayers, possibly because of interactions between the polar headgroup and carbonyl groups of the fatty acyl chains.